Unconventional decoding of the AUA codon as methionine by mitochondrial tRNA(Met) with the anticodon f(5)CAU as revealed with a mitochondrial in vitro translation system - Takemoto, Chie (Oxford University Press, 2009)
Mitochondrial (mt) tRNA(Met) has the unusual modified nucleotide 5-formylcytidine (f(5)C) in the first position of the anticodon. This tRNA must translate both AUG and AUA as methionine. By constructing an in vitro translation system from bovine liver mitochondria, we examined the decoding properties of the native mt tRNA(Met) carrying f(5)C in the anticodon compared to a transcript that lacks the modification. The native mt Met-tRNA could recognize both AUA and AUG codons as Met, but the corresponding synthetic tRNA(Met) lacking f(5)C (anticodon CAU), recognized only the AUG codon in both the codon-dependent ribosomal binding and in vitro translation assays. Furthermore, the Escherichia coli elongator tRNA(Met)(m) with the anticodon ac(4)CAU (ac(4)C = 4-acetylcytidine) and the bovine cytoplasmic initiator tRNA(Met) (anticodon CAU) translated only the AUG codon for Met on mt ribosome. The codon recognition patterns of these tRNAs were the same on E. coli ribosomes. These results demonstrate that the f(5)C modification in mt tRNA(Met) plays a crucial role in decoding the nonuniversal AUA codon as Met, and that the genetic code variation is compensated by a change in the tRNA anticodon, not by a change in the ribosome. Base pairing models of f(5)C-G and f(5)C-A based on the chemical properties of f(5)C are presented.